Flow enhancement in microchannels using okra, aloe vera and hibiscus mucilages - Ling, Fiona Wang Ming (2017)
Natural polymeric drag reducing additives (DRA) extracted or obtained from natural resources started to gain attention and interest from researchers in an attempt to replace the existing artificial DRA. The present work aims to study the feasibility of the natural polymer extracted from plant sources in enhancing the liquid flow in microchannels. Due to the development of microfluidics technology as an economical and reliable method for testing different theoretical phenomena related to engineering fields and medical fields, microchannel was utilized replacing the conventional method by using pipes which can reduce the usage of the chemical and reagents significantly. Polymers were extracted from okra, aloe vera and hibiscus leaves using water extraction method. Different mucilage solution concentration was prepared by weight/weight basis after extraction by adding deionized water which acted as working fluid. Four microchannels which have a thickness about 200 μm with different clogging area simulating the human heart vessel size were fabricated using xurographical approach and then molded with polydimethylsiloxane (PDMS). The experiment was conducted using an open-loop microfluidic system which connected to the costum made microchannels. The flow enhancement performance of different concentration of the additives ranging from 100 to 500 ppm was evaluated by recording the flow rate corresponding to the operating pressure (50 to 500 mbar). The flow behavior of the liquid flow with the addition of the additives was observed by utilizing micro-particle image velocimetry (μ-PIV) systems. It is important to highlight that the examined natural polymers have drag reduction properties. A non-linear relationship was obtained from this work between the concentration of the additives and percentage of flow rate increment (%FI). Increasing the polymer concentration increases the %FI until a limit which so-called critical concentration where beyond this point continuous increasing the concentration have an adverse effect on drag reduction. From the experimental results, hibiscus mucilage gives highest drag reduction performance by achieving higher %FI as hibiscus mucilage contained the highest composition of polysaccharides group. In most of the cases, increasing of the operating pressure resulted in the decreasing of %FI. Maximum flow increment up to 63.48% was achieved using 300 ppm of hibiscus mucilage at the operating pressure of 50 mbar. From the data obtained from μ-PIV systems, higher velocity was observed when the liquid was entering the narrowed area of the microchannel. The velocity remained high when the liquid exiting the semi-clogged part. The data from μ-PIV systems agreed with the experimental results where the addition of the additives increased the flow in the microchannel. The experimental results validate the potential use of these additives in medical fields to enhance the blood flow in semi-clogged blood streams which can be an alternative treatment for cardiovascular diseases. It was recommended that more new natural polymeric DRA should be investigated and explored the possibility of these polymers to dissolve or corrode the cholesterol which cause narrowing of the blood vessels.